Penegakan Hukum terhadap Pelaku Tindak Pidana Kekerasan secara Bersama-sama di Wilayah Hukum Polres Bantul - Narendra Pratama; Harti Winarni (Majelis: Jurnal Hukum Indonesia, 2025)
In the modern era, law enforcement faces increasingly complex challenges driven by socio-economic inequality, rapid urbanization, advancements in information technology, and shifting societal values. One significant consequence is the rise in violent crimes committed collectively (mobbing), which remains concerning issue in Indonesia, including Bantul, DIY. This research adopts a legal and empirical approach, examining causal factors and challenges faced by the Bantul Police’s Criminal Investigation Unit in handling mob violence cases. These acts are regulated under Article 170 of the KUHP, characterized by their open (openlijk) and collective (met vereenigde krachten) nature. Factors influencing mob violence include environmental conditions, personal revenge, the influence of social media, and educational background. Obstacles in the investigation include difficulties in identifying perpetrators, collecting sufficient evidence, and addressing the psychological state of both victims and witnesses. Statistical data highlights this ongoing issue: in 2022, there were 84 reported cases with 64 resolved; in 2023, 58 cases were reported with 42 resolved; in 2024, 53 cases were recorded with 41 resolved. From January to May 2025 alone, 21 reports were filed, with only 15 resolved. Although the number of reports has declined, the persistence of these cases demands more serious and coordinated responses from all stakeholders.